2018
DOI: 10.1111/ijfs.13827
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of high molecular weight water‐soluble chitosans against selected gram‐negative and gram‐positive foodborne pathogens

Abstract: Summary Antimicrobial activities of high molecular weight water‐soluble chitosans (HMWWS) against selected Gram‐negative and Gram‐positive foodborne pathogens (initial inoculation of ca. 6.5 Log CFU mL−1) were evaluated. Chitosans with 789 kDa and/or 1017 kDa were dissolved in aspartic acid (AS) to obtain 1–4% w/v solutions. Among HMWWS, only 4% 789 kDa AS chitosan reduced E. coli counts by 2 Log CFU mL−1 from 7.33 at 0 h to 5.16 Log CFU mL−1 at 96 h, and they were not effective against S. Typhimurium. Dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Also, the presence of S. typhimurium was negative in all fresh and stored fillets. In our previous study, we found that chitosan coating (4% w/v for 789 kDa and 3% w/v for 1,017 kDa) exhibited effective antimicrobial activity against some foodborne pathogenic bacteria (Karsli et al., 2019; Rubio et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the presence of S. typhimurium was negative in all fresh and stored fillets. In our previous study, we found that chitosan coating (4% w/v for 789 kDa and 3% w/v for 1,017 kDa) exhibited effective antimicrobial activity against some foodborne pathogenic bacteria (Karsli et al., 2019; Rubio et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al., (2017) reported that 2% w/v chitosan (300 to 400 kDa, 85% DD) coating caused a reduction of 1.27 log CFU/g in total viable count of refrigerated grass carp at the end of 15‐day storage, compared to the control. The antimicrobial mechanism of chitosan may be explained by the interaction of the positively charged amine group with the negatively charged microbial cell wall and membrane components, which induces the leakage of cellular proteins and other intracellular constituents (Karsli et al., 2019; Rubio et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial activity of chitosan was explained by many mechanisms, such as the availability of an amino group on chitosan which can absorb the essential nutrient needed for microbial growth; the interaction between the positive charge of the chitosan molecule and negative charge of the microbial cell membrane, which results in changes in membrane permeability; chitosan film formation on the surface of the microbial cell membrane, which prevents the nutrient from entering the cell (Atay, 2020; Li & Zhuang, 2020). Previous studies reported that chitosan exhibits antibacterial activities (Rubio et al ., 2018; Karsli et al ., 2019; Li et al ., 2020; Karsli et al ., 2021a,b). The antimicrobial and antifungal effects of chitosans were also observed in this study (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan’s antioxidant function was attributed to its structure and physicochemical properties (Xia et al ., 2011; Ngo & Kim, 2014) and was inversely dependent on its molecular weight (García et al ., 2015; Du & Vuong, 2019). Chitosan has a wide antimicrobial spectrum against Gram‐negative, Gram‐positive bacteria and fungi (Rubio et al ., 2018; Karsli et al ., 2019). Chitosan’s antimicrobial activity is known to be affected by several factors that take action in a systematic and independent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Rubio et al. (2018) have demonstrated that water‐soluble chitosans resisted against some gram‐negative and gram‐positive foodborne pathogens. Many reports have demonstrated that chitosan‐based coating composing tea polyphenols and clove EO (essential oil) showed more effective protection on spoilage and Maillard reaction of Pacific white shrimp ( Penaeus vannamei ) during refrigeration (Encarnacion et al., 2012; Sun et al., 2017).…”
Section: Introductionmentioning
confidence: 99%